2001
DOI: 10.1021/jp012664g
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies of Reductive Deposition of Copper(II) Ions Photoassisted by Titanium Dioxide

Abstract: Photoreduction of copper(II) ions onTiO2 was studied in the presence of sacrificial donors such as HCOONa, Na2C2O4, and Na2H2edta. Formate was the best donor with respect to the reduction rate but an induction period was observed. The induction period increased with an increase in the Cu(II) concentration or with a decrease in the TiO2 weight in suspension. The presence of sulfates, phosphates, and chlorides increased the induction period. The ESR measurements indicate that the Cu(II) ions exist as [Cu(H2O)6]2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…In the absence of an electrochemical setting, this oxidation process must take place on the same photocatalyst in which reductive deposition of the metal is occurring. Research from several groups [233,555,1113,1118,1124,1132,1135,1136,1138,[1149][1150][1151]1156,1158] has shown that choice of the sacrificial electron donor (usually an organic) is key to efficient metal photoreduction. This is not simply an issue of balancing redox potentials (although that is important), but also selecting an electron donor that does not compete for surface sites or otherwise interfere with the metal reduction process.…”
Section: Photoreduction Reactantsmentioning
confidence: 99%
“…In the absence of an electrochemical setting, this oxidation process must take place on the same photocatalyst in which reductive deposition of the metal is occurring. Research from several groups [233,555,1113,1118,1124,1132,1135,1136,1138,[1149][1150][1151]1156,1158] has shown that choice of the sacrificial electron donor (usually an organic) is key to efficient metal photoreduction. This is not simply an issue of balancing redox potentials (although that is important), but also selecting an electron donor that does not compete for surface sites or otherwise interfere with the metal reduction process.…”
Section: Photoreduction Reactantsmentioning
confidence: 99%
“…The electron donor ability of several carboxylic acids to the Cu(II) reduction photoassisted by TiO 2 has been compared recently and formate was found better electron donor than oxalate [104]. One of the interesting classes of copper complexes is that with aminocarboxylate ligands, such as glycine, glutamine, alanine, EDTA, NTA, IDA [100].…”
Section: Photoredox Copper Cyclesmentioning
confidence: 99%
“…The application of the TiO 2 photocatalytic reduction process is reported to effectively remove various toxic metal ions, such as Hg(II) [9,10], Se(IV) [11], Se(VI) [12,13], Cd(II) [14,15], Zn(II) [14], Cu(II) [16,17] and Cr(VI) [18][19][20]. Here, the photocatalytic system cannot be used directly to remove a toxic metal from a wastewater, but should be followed by an effective separation method (e.g.…”
Section: Introductionmentioning
confidence: 99%